PERANAN HAKIM DALAM PEMBERANTASAN TINDAK PIDANA NARKOBA MELALUI PUTUSAN YANG BERKEADILAN - Yanto, Oksidelfa (Jurnal Hukum dan Peradilan, 2017)
Indonesia is the fourth largest country in the capacity of the population number in the world. As the country with the largest population, various problems often plague the nation of Indonesia. One such problem is the problem of law enforcement and narcotics and drugs cases. Up to now Indonesia is confronted with drug trafficking that is very alarming. Drug crimes are so uncontrolled in social life. It is undeniable that narcotics have been threatening the future of the nation. There have been already many victims even until some of them dies. Drug abuse has reached very dangerous phase. There is no other way, government and officials must immediately take a serious and earnest step. It is a pity that the nation's children must always be the victims of drug distribution by the syndicate. Laws must be enforced as fairly as possible. Because the law is the supreme commander that must not be defeated by anything.Keywords: role of the judge, crime, drugs